2018
DOI: 10.5539/jas.v10n6p57
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Perceptions of Rice Production Constraints and Stem Borers Management Practices in Tanzania

Abstract: Rice farmers in Tanzania continue to experience losses due to stem borers. However, the information on farmers' knowledge and perceptions of rice stem borers is limited and farmers' efforts on managing this insect have been ineffective. The aim of this study was to investigate constraints affecting rice production and farmers' approaches of stem borer management in irrigated low land rice ecosystems in Tanzania. Research method: A focus group discussion with farmers using a semi-structured questionnaire was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…However, lack of awareness on and/or unavailability of other control measures are the likely reason for the sole reliance by farmers on synthetic insecticides. Similar results have been reported in many developing countries where growing dependence on synthetic insecticides/non-IPM for the control of crop pests is alarming (Khan et al, 2015;Kumela et al, 2018;Zhang et al, 2018, Ochilo et al, 2018Bonaventure et al, 2018). Farmer's reliance on intensive pesticide application was also common for other crops such as cotton, mango, maize, tomato, eggplants, and cabbages and other vegetables in various countries (Munyuli, 2016;Akotsen-Mensah et al, 2017, Rumbidzai et al, 2017Kumela et al, 2018).…”
Section: Insectsupporting
confidence: 68%
“…However, lack of awareness on and/or unavailability of other control measures are the likely reason for the sole reliance by farmers on synthetic insecticides. Similar results have been reported in many developing countries where growing dependence on synthetic insecticides/non-IPM for the control of crop pests is alarming (Khan et al, 2015;Kumela et al, 2018;Zhang et al, 2018, Ochilo et al, 2018Bonaventure et al, 2018). Farmer's reliance on intensive pesticide application was also common for other crops such as cotton, mango, maize, tomato, eggplants, and cabbages and other vegetables in various countries (Munyuli, 2016;Akotsen-Mensah et al, 2017, Rumbidzai et al, 2017Kumela et al, 2018).…”
Section: Insectsupporting
confidence: 68%
“…Despite the high demand for rice in Tanzania, yield remains low in the range of 1-1.79 tonnes/ha as compared to potential yield of 6-10 tonnes/ha due to several production constraints (MAFSC, 2009;FAO, 2015). Of all the production constraints of rice, one major reason for the low yield in Tanzania is the damage by stem borers (January, Rwegasira, & Tefera, 2018a), but there is limited information on damage symptoms, its biology including life cycle which limits on insect pest monitoring and timely planning for appropriate management practices.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is shortage of improved seed varieties which are tolerant to drought, cold weather, insects, pests and diseases (Duku et al, 2016;January et al, 2018).…”
Section: Lack Of Improved Seed Varietiesmentioning
confidence: 99%